The Support to Improve Self Efficacy and Healing of Drugs Addict - Rosdiana Rosdiana; Bhisma Murti; Mahendra Wijaya; Suwarto Suwarto (International Journal of Public Health Science (IJPHS), 2016)
Appropriate counseling and education can be adopted to achieve a change in attitude, knowledge and perception. Still there is a wrong perception of a given intervention. Peer support through a process of social learning, the process of growing understanding of how to process information from experience, observational include: attention (attention), given (retention), reproduction of motion (reproduction), motivation (motivation), and communication. The purpose of this study was to analyze resident self-efficacy to regardless of drug addiction through family support. This study employed qualitative approach with case study design. Subjects in this study were residents, ex drugs user, peer support, and resident family. The results showed that peer support from fellow residents and the support of the major on duty (MOD) very meaningful and helpful for resident in the healing process.